2017
DOI: 10.1111/1759-3441.12175
|View full text |Cite
|
Sign up to set email alerts
|

Causality between Public Debt and Real Growth in the OECD: A Country‐by‐country Analysis

Abstract: We analyse the direction of causality between public debt and real economic growth in a sample of 20 OECD countries for a period of 40 years starting in 1970. Given the persistence of real growth rates, we estimate canonical cointegrating regressions to allow for the possibility of stochastic cointegrating vectors. We then make inferences about the direction of causality by means of both Granger tests and VAR-based tests that do not depend on whether the series are integrated or cointegrated. We found that whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
(84 reference statements)
0
15
1
2
Order By: Relevance
“…This assertion is underscored by the work of Donayre and Taivan (2017) which established that the causal relationship between public debt and real GDP growth is intrinsic to each country. They further disclosed that in highly market-driven economies, the direction of causality is from low GDP growth to public debt; however, in more socialist states, causality runs either from low GDP growth to public debt accumulation or is bi-directional (Donayre and Taivan, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This assertion is underscored by the work of Donayre and Taivan (2017) which established that the causal relationship between public debt and real GDP growth is intrinsic to each country. They further disclosed that in highly market-driven economies, the direction of causality is from low GDP growth to public debt; however, in more socialist states, causality runs either from low GDP growth to public debt accumulation or is bi-directional (Donayre and Taivan, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To respond to the global economic recessions after the Second World War, many economies (including developed and developing) resorted to borrowing either domestically or externally to fund budget deficits. These strives had led to the accumulation of public debt for many countries, resulting in the economic recession and debt crises experienced in the early 2000s by many developed and developing countries (Donayre and Taivan, 2017). As a result, academic and policy debate on the causal relationship between public debt and economic growth had been renewed (G omez-Puig and Sosvilla-Rivero, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to our knowledge, no strong case has yet been made for analysing the effect of debt accumulation on economic growth taking into account the particular characteristics of each EA economy and examining whether the effects differ depending on the time horizon, in spite of the fact that this potential heterogeneity has been stressed by the literature. For instance, Eberhardt and Presbitero (2015) and Égert (2015) support the existence of nonlinearity in the debt-growth nexus, but state that there is no evidence at all for a threshold level common to all countries over time; while Gómez-Puig and Sosvilla-Rivero (2015) and Donayre and Taivan (2017), who analyse the causal relationship between public debt and economic growth, also suggest that the causal link is intrinsic to each country.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other researchers added some more light on the problem and found that for developed OECD countries increases in public debt is often followed by low real growth and there exist bidirectional causality from low growth to debt accumulation (Donayre & Taivan, 2017).…”
Section: Public Debtmentioning
confidence: 99%